A simple and reliable method reducing sulfate to sulfide for multiple sulfur isotope analysis. (30th January 2018) - Geng, Lei; Savarino, Joel; Savarino, Clara A.; Caillon, Nicolas; Cartigny, Pierre; Hattori, Shohei; Ishino, Sakiko; Yoshida, Naohiro
Abstract : Rationale: Precise analysis of four sulfur isotopes of sulfate in geological and environmental samples provides the means to extract unique information in wide geological contexts. Reduction of sulfate to sulfide is the first step to access such information. The conventional reduction method suffers from a cumbersome distillation system, long reaction time and large volume of the reducing solution. We present a new and simple method enabling the process of multiple samples at one time with a much reduced volume of reducing solution. Methods: One mL of reducing solution made of HI and NaH2 PO2 was added to a septum glass tube with dry sulfate. The tube was heated at 124°C and the produced H2 S was purged with inert gas (He or N2 ) through gas‐washing tubes and then collected by NaOH solution. The collected H2 S was converted into Ag2 S by adding AgNO3 solution and the co‐precipitated Ag2 O was removed by adding a few drops of concentrated HNO3 . Results: Within 2–3 h, a 100% yield was observed for samples with 0.2–2.5 μmol Na2 SO4 . The reduction rate was much slower for BaSO4 and a complete reduction was not observed. International sulfur reference materials, NBS‐127, SO‐5 and SO‐6, were processed with this method, and the measured against accepted δ 34 S values yielded a linear regression line which had a slope of 0.99 ± 0.01 and a R 2 value of 0.998. Conclusions: The new methodology is easy to handle and allows us to process multiple samples at a time. It has also demonstrated good reproducibility in terms of H2 S yield and for further isotope analysis. It is thus a good alternative to the conventional manual method, especially when processing samples with limited amount of sulfate available.